Fictive clusters: Crafty strategies in the New Zealand beer industry. Issue 3 (26th May 2016) - Murray, Warwick E.; Overton, John
ABSTRACT: The authors bring together two theoretical and empirical strands in economic geography – established work on clusters and nascent research on 'fictive place' – in order to introduce the concept of 'fictive clusters'. To explore this concept, they examine the New Zealand craft beer sector, which has evolved from non-existence since the year 2000. This growth has precipitated the rise of a dynamic and innovative cluster at the local scale in Wellington. The fictive cluster is explored through the Wellington case study, and the authors pose various questions for future work based on this discursive geographical device. The construction and complicit reproduction of what they term a 'fictive cluster' has been central to the evolving strategies of the involved agents. Through the use of this term, the evolution of Wellington place-based brands that are increasingly territorially specific are seen as building competitive advantage based on constructed histories, environments, and other geographic characteristics.